Faktor-Faktor yang Berhubungan dengan Keikutsertaan Kelas Ibu Hamil di Wilayah Kerja Puskesmas Telaga Dewa Kota Bengkulu Tahun 2025 - Ade Irma Suryani; Berlian Kando Sianipar; Jumita Jumita (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The lack of participation by pregnant women in prenatal classes can lead to delays in treatment if something happens to the mother, as she may not be aware of the warning signs related to pregnancy, childbirth, the postpartum period, and newborn care. To identify the factors associated with participation in prenatal classes in the service area of the Telaga Dewa Community Health Center in Bengkulu City. The study employed an analytical survey design with a cross-sectional approach. The study population consisted of 45 pregnant women with gestational ages of 28–36 weeks as of September at the Telaga Dewa Community Health Center and PMB. The sample was selected using total sampling. Univariate analysis revealed that nearly half of the respondents (21, or 46.7%) had adequate knowledge; the majority of respondents (28, or 62.2%) were non-working pregnant women; and nearly half of the respondents (18, or 40%) were not active participants in prenatal classes. There is a relationship between knowledge and participation in prenatal classes in the service area of the Telaga Dewa Community Health Center in Bengkulu City (p-value = 0.006), there is an association between employment status and participation in prenatal classes in the service area of the Telaga Dewa Community Health Center in Bengkulu City (p-value = 0.015), and there is an association between spousal support and participation in prenatal classes in the service area of the Telaga Dewa Community Health Center in Bengkulu City (p-value = 0.000). It is hoped that the results of this study can serve as input for health workers, particularly midwives, to improve the provision of health care and serve as a foundation for the implementation of guidance, coaching, and counseling programs in an effort to increase pregnant women’s participation in prenatal classes.